Modeling and Analysis of the Spread of Malware with the Influence of User Awareness - Qingyi Zhu; Xuhang Luo; Yuhang Liu (Complexity)
By incorporating the security awareness of computer users into the susceptible-infected-susceptible (SIS) model, this study proposes a new malware propagation model, named the SID model, where D compartment denotes the group of nodes with user awareness. Through qualitative analysis, the basic reproductive number R0 is given. Furthermore, it is proved that the virus-free equilibrium is globally asymptotically stable if R0 is less than one, whereas the viral equilibrium is globally asymptotically stable if R0 is greater than one. Then, some numerical examples are given to demonstrate the analytical results. Finally, we put forward some efficient control measures according to the theoretical and experimental analysis.